1992
DOI: 10.1002/polb.1992.090300301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cyclic stress on enthalpy relaxation in polycarbonate

Abstract: Possible effects of cyclic stress on physical aging in polycarbonate were investigated using differential scanning calorimetry (DSC) measurements. When the enthalpy overshoot by DSC of specimens of different previous thermophysical aging histories is measured as a function of the cyclic stress amplitudes, two characteristic regimes are observed. By correlating with optical microscopic observations, these regimes are identified as the incubation and crazing stages (denoted regimes I and II, respectively). The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Some researchers have measured changes induced in polymers resulting from cyclic fatigue. On the macroscopic level, a number of researchers measured changes in the dynamic mechanical response of a variety of polymers and composites (12)(13)(14)(15)(16)(17)(18)(19)(20). These studies have shown that, in certain cases, changes in the dynamic mechanical response can be correlated with corresponding changes in the microstructure or morphology of the materials during fatigue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have measured changes induced in polymers resulting from cyclic fatigue. On the macroscopic level, a number of researchers measured changes in the dynamic mechanical response of a variety of polymers and composites (12)(13)(14)(15)(16)(17)(18)(19)(20). These studies have shown that, in certain cases, changes in the dynamic mechanical response can be correlated with corresponding changes in the microstructure or morphology of the materials during fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this relation was shown by Ehrenstein et al for composites (19) and more recently by the author for semicrystalline polymers (20, 2 1). In an interesting and related study, Yee et al (18) noticed that measurable changes in the enthalpy and mechanical proper-ties could be measured in polycarbonate as a result of fatigue loading. Yee noted that these changes resembled those produced by thermophysical aging and referred to the effects as fatigue agfng.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been done to examine the effect of physical aging on the macroscopic mechanical behavior of glassy polymers and similarly for the enthalpy changes upon aging . Most of the studies are trying to explain their results based on the free‐volume theory, in which the changes of the properties of the material are interpreted solely by the changes in free volume .…”
Section: Introductionmentioning
confidence: 99%
“…Knauss et al investigated the aging effect on poly (vinyl acetate) with different pressure and aging time. Liu et al discussed the effect of cyclic stress on physical aging in polycarbonate using differential scanning calorimetry (DSC) measurements.…”
Section: Introductionmentioning
confidence: 99%